O clima de cidades pequenas: configuração urbano-rural com uso de transectos móveis em Agudo/RS - Kegler, Jonathan Júlio (2016)
The urban climate study has a great importance in regard to the understanding of man's relationship with nature and climate-city relationship, especially from the changes promoted with urbanization. This perspective has motivated this study on the Urban Climate of Agudo/RS, especially in raising the thermodynamic channel, according to the SCU proposed by Monteiro (1976), in four different climatic situations, two in winter and two in summer. For this research, it became relevant theoretical background to the topic, as well as field survey for recognition of information relevant to the search. In the urban and rural environment near Agudo, mobile transects were made to collect temperature and relative humidity at three times: at 6AM, 3PM and 9PM in four different dates, two in winter and two in summer with the aid of datalogger and GPS. After data collection, they were tabulated and spatialized with GIS support for further analysis with the geoecological and geourban data of Agudo, in order to understand if there was or not manifestation of urban climate in this city. There was training in two moments of freshness island phenomenon, one in the winter, under the control of the "Anticyclonic Polar Sea Weather", associated with the Polar Atlantic anticyclone with maritime trip, and the other in summer, in the area of "Low pressure Continental weather" associated with the field of Tropical and Continental air Mass. Both registered freshness islands were weak magnitude, with 1°C difference less than its near surroundings. In this sense, the different weather systems involved do not provide different magnitudes, which can be explained by Agudo s urbanization not be very pronounced if the same phenomenon was recorded in a larger urban area, in the town of Agudo does not favor the formation an island of coolness medium or strong magnitude, regardless of atmospheric ruling system, given its degree of urbanization. Since the formation of heat islands in Agudo was restricted to the summer period, and both associated with tropical atmospheric domains, with Tropical Atlantic air mass, forming the "anticyclonic TropicalSea weather" and Tropical Continental air Mass, forming the "Low pressure Continental weather". However, the magnitude of the heat island was stronger when the presence of tropical masses with formation inside the south- American continent, which brings more heat than the tropical oceanic ones.